Atlas des peuples autochtones du Canada: Les métis - Royal Canadian Geographical Society (The Royal Canadian Geographical Society, 2018)
Created in partnership with the Assembly of First Nations, Inuit Tapiriit Kanatami, the Métis Nation, the National Centre for Truth and Reconciliation and Indspire